ANALISA PELAKSANAAN KEGIATAN CUSTOMER GATHERING PT. FOODY DIREKTORI INDONESIA - Angela Clarissa; Marcha Chryztantya; Vegys Virgynitha Gultom (JIKE: Jurnal Ilmu Komunikasi Efek, 2019)
One important part of an organization is external publics such as customers. Holding some events/activities by organization to their publics is often a necessary things to do. PT Foody Direktori Indonesia is a restaurant directory service company in Indonesia that holds customer gathering activities. This research focused on the implementation of customer gathering acitivites conducted by PT Foody Direktori Indonesia. The objective of this research is to see how the implementation of customer gathering and also to see the obstacles and efforts in the implementation of gathering. To analyze the gathering activities, this research use the concept from Dennis L. Wilcox of 8 stages public relations activities planning that contain situation, objectives, audience, strategy, tactics, calendar/timetable, budget, and evaluation. This research uses a qualitative method and interviews as the data collection technique. The result of this research is PT Foody Direktori Indonesia conducts their customer gathering activity according to the 8 stages of public relations activites planning by Dennis L. Wilcox. From this research it was also found that PT Foody Direktori Indonesia have some obstacles during planning gathering activities and already have made an effort to resolve these obstacles. Keywords: Public Relations, Customer Relations, Customer Gathering